Pengaruh Konten Video Tiktok Sashfir terhadap Referensi Gaya Berhijab - Y.S, Gladys Faras; Muslimah, Tikka (Universitas Pahlawan Tuanku Tambusai, 2025)
This aims of this research is to determine the effect of TikTok video content from the @Sashfir TikTok account on hijab style references among its followers. The background of this research is based on the phenomenon of increasing TikTok users in Indonesia. Reporting from RRI.co.id as of July 2024, Indonesia was named the country that used TikTok the most. The number reached 157.6 million users. and the popularity of hijab tutorial content as a source of style inspiration. The research uses a quantitative approach with descriptive statistics and normality tests, simple regression analysis tests, partial tests (t), and coefficient of determination () tests with a survey method of 100 respondents who are followers of the @Sashfir TikTok account, then using the Simple Random Sampling technique. The theory used is Uses and Gratifications, with three sub-variables namely intensity, message content, and attractiveness. The results of the analysis show that there is a significant effect of message content and attractiveness, but no significant effect of intensity on hijab style reference.